Serum Uric Acid Level and Multiple Sclerosis: A Mendelian Randomization Study - Niu, Peng-Peng; Song, Bo; Wang, Xue; Xu, Yu-Ming (Frontiers in Genetics, 2020)
Previous observational studies have shown that the serum uric acid level are decreased in persons with multiple sclerosis. We used the two-sample Mendelian randomization (MR) method to determine whether the serum uric acid level is causally associated with the risk of multiple sclerosis. We screened 26 single-nucleotide polymorphisms (SNPs) in association with serum uric acid level (P < 5×10−8) from a large genome-wide meta-analysis involving 110,347 individuals. The SNP-outcome effects were obtained from two large international genetic studies of multiple sclerosis involving 38,589 individuals and 27,148 individuals, respectively. A total of 18 SNPs, including 9 nine proxy SNPs, were included in the MR analysis. The estimate based on SNP rs12498742 that explained the largest proportion of variance showed that the odds ratio of uric acid (per mg/dl dL increase) for multiple sclerosis was 1.00 (95% confidence interval 0.90–1.11; p = 0.96). The main MR analysis based on the random effects inverse variance weighted method showed that the pooled odds ratio was 1.05 (95% confidence interval 0.92–1.19; p = 0.50). Although there was no evidence of net horizontal pleiotropy in MR-Egger regression (p = 0.48), excessive heterogeneity was found via Cochran’s Q statistic (p = 9.6 × 10-4). The heterogeneity showed a substantial decrease after exclusion of two outlier SNPs (p = 0.17). The pooled odds ratios for the other MR methods ranged from 0.89 (95% confidence interval 0.65–1.20; p = 0.45) to 1.05 (95% confidence interval 0.96–1.14; p = 0.29). The results of sensitivity analyses and additional analyses all showed similar pooled estimates. MR analyses by using 81 multiple sclerosis associated SNPs as instrumental variables showed that genetically-predicted risk of multiple sclerosis was not significantly associated with serum uric acid level. The pooled odds ratio was 1.00 (95% confidence interval 0.99–1.02; p = 0.74) for the main MR analysis. This MR study does not support a causal effect of genetically determined serum uric acid level on the risk of multiple sclerosis, nor does it support a causal effect of genetically determined risk of multiple sclerosis on serum uric acid level.